Improvement of the manufacturing of aluminum pots using lean manufacturing tools - Cusihuallpa-Vera, Ximena (2021)
The research is based on the problems encountered in the production process of companies in the metalworking sector. The problem arises from the low availability of machines in the production process due to working conditions (39.5%), poor maintenance management (40.3%) and poor-quality control (20.2%) that generate low profitability for business. As a solution, Lean Manufacturing tools are implemented to improve the process and increase profitability. The improvement proposal consists of a series of stages: first, the definition of indicators for the measurement of the variables; then, the design and implementation of a pilot in the production process and, in parallel, a simulation system will be designed to evaluate the long-term results. The document concludes that the implementation of the proposed tools will increase the availability of machines and an OEE to 55%, avoiding defective products and reducing reprocessed products by 4%.